(untitled) - Bal, Henri E. (Massachusetts, 1994)
The book provides a concise guide through the bewildering variety of modern programming languages, focusing on essential concepts while omitting irrelevant detail. The book highlights these major programming paradigms: imperative languages, illustrated with ANSI C and Ada 9X examples; object-oriented languages (with C++); functional languages (with Miranda); logic languages (with Prolog); languages for parallel and distributed systems (with Ada 9X and others). A final chapter provides an overview of special-purpose or non-standard languages including PIC, APL, SETL and SQL. Each chapter contains a summary and exercises. The answers to most exercises are collected in appendix B. Each chapter also contains a bibliographical section, with references to relevant books and journals
Keywords: Programming languages ( electronic computers )